Impact of Mindfulness-Based Stress Reduction Techniques on General Well-Being of Employees Working on a Behavioral Health Unit - Clyde R. Smith; Abhishek Rai; Jaspreet Brar; Avianna Castro (Indian Journal of Integrative Medicine, 2021)
Background: Mindful-based Stress Reduction (MBSR) interventions have become a breakthrough treatment modality in reducing stress and improving overall general well-being. MBSR practiced by individuals gets impacted on a physical, social, mental, emotional, and spiritual level. MBSR approaches have been studied and support to improve the general wellbeing of individuals and enhance the quality of life. Methods: Behavioral Health employees participated in daily independent mindfulbased stress reduction sessions over six weeks. The mindfulness audio files are recorded specifically for this research project. Employees completed a demographic form, Perceived Stress Scale (PSS), and Subjective Happiness Scale (SHS) pre-andpost six-week period. The PSS and SHS were used to complete and collect qualitative data on the effectiveness of MBSR. Results: This study reported the following results. A total of 22 behavioral health employees volunteered to participate in the study. The average score pre-study on SHS was (16.41+2.45). Post mindfulness intervention, the average score on SHS increased to (18.71+2.49). The average score pre-study on PSS was (20.18+3.17) post mindfulness intervention the average score in PSS came down to (10+4.29). The results were highly significant. Conclusion: The results suggest a high correlation with a reduction in behavioral health employees’ perceived stress and physical response to stress in their personal and professional life when individuals practice MBSR techniques. Reduction in perceived stress of mental health workers results in the improved general wellbeing of the employee and improve capabilities for the employee to handle stress at work, therefore, improving patient care outcomes.